The evolution of cereal yields in Italy over the last 150 years: The peculiar case of rice. (10th June 2021) - Mariani, Luigi; Ferrero, Aldo; Cola, Gabriele
Abstract: This study examined Italian yields for wheat ( Triticum spp.), maize ( Zea mays L.), and rice ( Oryza sativa L.) over the period 1870–2018, in order to identify the periods when the most significant growth in yields occurred, compared to France, United Kingdom, and United States. From 1870 to 2018, yields in Italy increased by 347, 865, and 178% for wheat, maize, and rice, respectively. In wheat and maize, 84 and 95% of the increase, respectively, occurred since the end of World War II. Similar trends can also be observed in France, United Kingdom, and the United States. However the timing is slightly different. For wheat and maize in the United States, rapid yield growth occurred during the 1930s, whereas wheat yield growth occurred in the United Kindom during the 1940s, and in France yield growth occurred after World War II. The significant post‐war trend of increasing yields in Italy, which is still going on for wheat, almost stopped for maize about 20  yr ago, probably due to the lack of availability of genetically modified (GM) varieties and related technologies. If the current approach against the adoption of new plant‐breeding techniques is maintained, the yield gap between Italy and Europe, as a whole, is likely to widen further. In the case of rice, a significant increase in yields began to occur as early as the end of the 19th century. Between 1895 and 1940 yields in this crop increased by about three times. In the United States, a similar increase in rice yields occurred only after World War II. Core Ideas: Since 1870, Italian yields have increased by 347% in wheat, 865% in maize, and 178% in rice. In Italy, a notable increase in rice yields started since the late 1800s, 50 yr before the United States. In Italy, the increase of rice yield lead the way to the other crops. The major increase in wheat yields began in Italy, United States, United Kingdom, and France at the end of WW II. In Italy the yield of maize increases in the 1940s lagging behind the United States.